Active Learning Based on Deep Learning: A Critical Review of The Role and Readiness of Islamic Religious Education Teachers - Elvy Gustina; Silfia Hanani; Zulfani Sesmiarni (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the perceptions and readiness of Islamic Religious Education (PAI) teachers in implementing the deep learning concept in active learning. The method used is a qualitative approach through a literature review, where data were collected from various relevant sources such as scientific journals, books, and research articles discussing deep learning concepts, active learning, teacher readiness, and their implications in the context of PAI learning. The analysis was conducted descriptively and critically using content analysis techniques to identify key themes related to teachers’ perceptions, supporting and inhibiting factors of readiness, and the impact of implementing active learning based on deep learning. The findings show that PAI teachers generally have a positive perception of deep learning as an approach capable of deepening understanding and Islamic values meaningfully; however, their readiness to implement it varies and is influenced by competencies, training, technological infrastructure, and institutional policy support. The implications of applying this concept include a shift in teachers’ roles to facilitators, development of interactive and reflective learning designs, and authentic and holistic evaluation methods while considering cultural sensitivity and contextual integration of Islamic values. This study recommends strengthening teacher capacity through continuous training, enhancing technological facilities, and policy synergy to realize transformative, critical, and character-oriented PAI learning in the digital era.